2020
DOI: 10.1101/2020.07.11.20151332
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Diagnosis of COVID-19 using CT scan images and deep learning techniques

Abstract: Early diagnosis of the coronavirus disease in 2019 (COVID-19) is essential for controlling this pandemic. COVID-19 has been spreading rapidly all over the world. There is no vaccine available for this virus yet. Fast and accurate COVID-19 screening is possible using computed tomography (CT) scan images. The deep learning techniques used in the proposed method was based on a convolutional neural network (CNN). Our manuscript focuses on differentiating the CT scan images of COVID-19 and non-COVID 19 CT using dif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Entirely novel deep neural network architectures have been explored in some studies for COVID-19 case detection. Shah et al ( 35 ) proposed a 10-layer 2D CNN called CTnet-10, but found that it was outperformed by pre-existing architectures. Zheng et al ( 37 ) proposed a 3D CNN called DeCovNet which operates on full 3D CT volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Entirely novel deep neural network architectures have been explored in some studies for COVID-19 case detection. Shah et al ( 35 ) proposed a 10-layer 2D CNN called CTnet-10, but found that it was outperformed by pre-existing architectures. Zheng et al ( 37 ) proposed a 3D CNN called DeCovNet which operates on full 3D CT volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Eighteen papers applied deep learning techniques to CT imaging, all of which were framed as a classification task to distinguish COVID-19 from other lung pathologies such as (viral or bacterial) pneumonia, interstitial lung disease 35,[40][41][42][43][44][45][46][47] and/or a non-COVID-19 class 40,41,44,46,[48][49][50][51][52] . The full three-dimensional (3D) volumes were only considered in seven papers 40,43,47,50,[52][53][54] with the remainder considering isolated 2D slices or even 2D patches 45 . In most 2D models, authors employed transfer learning, with networks pre-trained on ImageNet 55 .…”
Section: Diagnostic Models For Covid-19 Diagnosis Models Using Cxrsmentioning
confidence: 99%
“…We have searched existing techniques in the online literature using different keywords such as “Machine learning and COVID-19”, “COVID-19 diagnosis with CT scans”, and “COVID-19 diagnosis with CT scans and machine learning”. While going through the online existing literature (peer-reviewed) published in reputed journals, we found a plethora of machine learning techniques to diagnose COVID-19 using chest CT scans with varying sources and amount of training data [ [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. All these previously published techniques can be categorized into three main classes as follows: Deep learning-based, transfer learning with fine-tuning a customized fully connected layer, shallow learning with handcrafted textured features.…”
Section: Related Workmentioning
confidence: 99%
“…Previously published studies employing deep learning-based machine learning techniques to detect COVID-19 mostly used Convolution Neural Network (CNN) [ 20 ] based architectures in their proposed design [ [23] , [24] , [25] , 29 , [31] , [32] , [33] , [34] , [35] , [36] , [37] ]. However, deep learning approaches to generalize well normally require an enormous amount of data which is not readily available right now [ 22 ].…”
Section: Related Workmentioning
confidence: 99%